Smart Contracts from a Civil Law Perspective: Validity and Implementation in Indonesia - Sudarto, Sudarto (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2025)
This study examines the validity and application of smart contracts within the Indonesian civil law framework. Smart contracts are block chain-based agreements that are implemented autonomously, eliminating the necessity for intermediaries. Although it provides efficiency and openness, its integration into the Indonesian legal system continues to encounter obstacles, particularly concerning regulations and dispute resolution methods. The legitimacy of an agreement in civil law is governed by Article 1320 of the Civil Code, which stipulates the necessity of mutual consent, legal ability, definite objects, and justifiable grounds. Nonetheless, there exists no regulation that explicitly governs smart contracts, necessitating additional examination of their legal standing.This study employs a normative legal methodology utilizing both conceptual and legislative approaches. The utilized data sources comprise primary legal materials, including the Civil Code and the Indonesian ITE Law, alongside secondary legal materials from books, scholarly publications, and prior study. The investigation aimed to ascertain the validity and legal binding nature of smart contracts inside the Indonesian civil system.The study's findings indicate that while smart contracts theoretically satisfy the components of an agreement as outlined in the Civil Code, issues persist regarding regulation and dispute resolution. Consequently, it is essential to formulate specific legislation or amendments to the ITE Law and Civil Code to facilitate smart contracts. Furthermore, the function of notaries and legal entities in authenticating smart contracts need elucidation to prevent legal ambiguity. In conflict resolution, hybrid methods like block chain-based arbitration may serve as an alternate solution. Consequently, the adoption of smart contracts in Indonesia need enhanced legal certainty to facilitate widespread utilization and ensure protection for the involved parties.